PENGARUH PEMBERIAN COOKIES TEPUNG LABU KUNING DAN KEDELAI TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE II - Devi Arista Putri; Susyani Susyani; Manuntun Rotua (POLTEKKES KEMENKES MEDAN, 2021)
Introduction Diabetes Mellitus is a chronic disease caused by reduced insulin production from the pancreas and insulin produced is not effective in reducing blood sugar levels. This situation will increase blood glucose levels. Alternative therapy management to control blood glucose by utilizing food ingredients that can help reduce blood sugar levels, one of which is pumpkin flour and soybeans. The purpose of this study was to determine the effect of giving pumpkin flour cookies to a decrease in blood sugar levels in Type 2 DM patients in Palembang Social Health Center. Method is a quasi-experimental research design with a pretest-posttest with control group using a comparison group. The subjects of this study were 76 people with Type 2 Diabetes Mellitus in the Social Health Center who were willing and fulfilled the inclusion and exclusion criteria. Data analysis uses t-dependent and t-independent tests. Results showed that there was an average difference in the determination of blood sugar levels in the treatment group at 59.89 mg / dl and in the comparison group at 17.89 mg / dl. The t-independent statistical test results obtained p-value <0.05 (0,000), that there was an Effect of Provision of Yellow Pumpkin Flour Cookies and Soybeans on Decreasing Blood Sugar Levels in Type 2 Diabetes Mellitus Patients in Palembang Social Health Center. Conclusion There Is An Effect Of Provision Of Pumpkin Flour Cookies And Soy To Lower Blood Sugar Levels In Type 2 Diabetes Mellitus Patients in Palembang Social Health Center.